2020
DOI: 10.1371/journal.pone.0230582
|View full text |Cite
|
Sign up to set email alerts
|

Parameter identification for gompertz and logistic dynamic equations

Abstract: In this paper, we generalize and compare Gompertz and Logistic dynamic equations in order to describe the growth patterns of bacteria and tumor. First of all, we introduce two types of Gompertz equations, where the first type 4-paramater and 3-parameter Gompertz curves do not include the logarithm of the number of individuals, and then we derive 4parameter and 3-parameter Logistic equations. We notice that Logistic curves are better in modeling bacteria whereas the growth pattern of tumor is described better b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 17 publications
(11 citation statements)
references
References 13 publications
(28 reference statements)
0
11
0
Order By: Relevance
“…We found that Logistic model fit the data slightly better than Gompertz model ( R 2 > 0.97, compared to R 2 > 0.96). In addition, previous studies have shown that Gompertz model is more precise for predicting and describing tumor growth, whereas Logistic model is better for modeling bacterial growth (Akın et al., 2020; Annadurai et al., 2000). As a result, we performed the statistical comparison only on the parameters generated by Logistic model.…”
Section: Resultsmentioning
confidence: 99%
“…We found that Logistic model fit the data slightly better than Gompertz model ( R 2 > 0.97, compared to R 2 > 0.96). In addition, previous studies have shown that Gompertz model is more precise for predicting and describing tumor growth, whereas Logistic model is better for modeling bacterial growth (Akın et al., 2020; Annadurai et al., 2000). As a result, we performed the statistical comparison only on the parameters generated by Logistic model.…”
Section: Resultsmentioning
confidence: 99%
“…Microbial growth has been intensively analyzed and modeled using bacterial monospecific cultures in the laboratory [ 71 , 72 , 73 ]. As a consequence, the expected growth of a bacterial isolate in the laboratory is represented by a sigmoidal curve composed of differentiated and characteristic growth phases ( Figure 1 ): the lag phase of growth (initiation of the metabolic machinery for growth), the exponential phase of growth (exponential increase in cell abundance and maximum growth rate), the stationary phase of growth (cells adapt to changing conditions due to scarcity of nutrients), and the decline (or death) phase (decrease in cell number).…”
Section: Microbial Growthmentioning
confidence: 99%
“…Bohner and Peterson (2001) is one of the most important books that explains the significant part of this calculus. The following articles show the results on the dynamic equations in time scale calculus; Akın and Bohner (2003), Akın et al (2020), Anderson (2005), Kayar et al (2022), Kayar and Kaymakçalan (2022a) and Kayar and Kaymakçalan (2022b). In the literature, many different kinds of calculus were defined.…”
Section: Introductionmentioning
confidence: 99%